Prognostic factors and treatment outcomes for patients with stage II extranodal nasal-type natural killer/T-cell lymphoma of the upper aerodigestive tract. Issue 8 (August 2014) - Fang, Hui; Jin, Jing; Wang, Wei-Hu; Wang, Shu-Lian; Zhou, Li-Qiang; Li, Ye-Xiong
Abstract The prognosis and optimal therapy for high-risk early-stage extranodal nasal-type natural killer/T-cell lymphoma (NKTCL) are not well defined. This study was conducted to evaluate the prognostic factors and treatment outcomes in patients with stage II NKTCL of the upper aerodigestive tract (UADT-NKTCL). One hundred and twenty-four patients with stage II UADT-NKTCL were enrolled. Primary tumors were located in the nasal cavity (n = 53) or extranasal UADT (n = 71). Eighty-four patients were treated with combined modality therapy (CMT), and 40 patients were treated with radiotherapy alone (n = 30) or chemotherapy alone (n = 10). The 5-year overall survival (OS) and progression-free survival (PFS) rates for all stage II patients were 60.1% and 47.8%, respectively. Primary location and disease extent were the important prognostic factors in univariate and multivariate analyses. CMT significantly improved survival. The 5-year OS and PFS rates were 71.2% and 56.7% for CMT, compared with 35.1% (p < 0.001) and 26.7% for single modality therapy (p < 0.001). Survival differences between CMT and single modality therapy were also observed in nasal and extranasal subgroups of UADT-NKTCL. This retrospective study showed significant improvements in OS and PFS in patients who received both chemotherapy and radiotherapy for stage II NKTCL. The findings need further validation in other datasets.